Correlation between ocular-surface disease index questionnaire, tear film break-up time and schirmer tests for evaluation of the tear film in patients of dry eye syndrome - Sapna Raghuwanshi; Rahul Agarwal; Shivkumar Raghuwanshi; Pallavi R Shidhaye (International Journal of Medical Research and Review, 2016)
Background: The purpose of this study is examining the correlation between clinical tests in patients of dry eye.Methods: Medical records of all cases of clinically diagnosed dry eye syndrome [DES] attending the corneal clinic of department of Ophthalmology, L.N. medical college Bhopal, India from September 2015 to December 2015 were retrospectively analyzed. Parameters such as OSDI (Ocular surface disease index), TBUT (Tear film breakup time), ST (Schirmer’s test), age, sex were evaluated.Result: One hundred and two patients were included in the study. Patients were predominantly males (51.92%) in group 1 and females (52 %) in group 2.Average female: male ratio was 0.92:1 in group 1 and 1.08: 1 in group 2. Mean age in group 1 was 41.1 years, in group 2 was 44.54 years. The OSDI was not correlated with TBUT and ST in group 1 and in group 2. The TBUT and ST test was not correlated in group 1 and group 2 (p> 0.05%).Conclusion: At present there is no diagnostic test available that can be considered as a gold standard test for DES. Which represents further studies may be necessary to increase our understanding and diagnosis.